How common road salts and organic additives alter freshwater food webs: in search of safer alternatives. Issue 5 (28th February 2017) - Schuler, Matthew S.; Hintz, William D.; Jones, Devin K.; Lind, Lovisa A.; Mattes, Brian M.; Stoler, Aaron B.; Sudol, Kelsey A.; Relyea, Rick A.
Summary: The application of deicing road salts began in the 1940s and has increased drastically in regions where snow and ice removal is critical for transportation safety. The most commonly applied road salt is sodium chloride (NaCl). However, the increased costs of NaCl, its negative effects on human health, and the degradation of roadside habitats has driven transportation agencies to seek alternative road salts and organic additives to reduce the application rate of NaCl or increase its effectiveness. Few studies have examined the effects of NaCl in aquatic ecosystems, but none have explored the potential impacts of road salt alternatives or additives on aquatic food webs. We assessed the effects of three road salts (NaCl, MgCl2 and ClearLane™) and two road salts mixed with organic additives (GeoMelt™ and Magic Salt™) on food webs in experimental aquatic communities, with environmentally relevant concentrations, standardized by chloride concentration. We found that NaCl had few effects on aquatic communities. However, the microbial breakdown of organic additives initially reduced dissolved oxygen. Additionally, microbial activity likely transformed unusable phosphorus from the organic additives to usable phosphorus for algae, which increased algal growth. The increase in algal growth led to an increase in zooplankton abundance. Finally, MgCl2 – a common alternative to NaCl – reduced compositional differences of zooplankton, and at low concentrations increased the abundance of amphipods. Synthesis and applications . Our results indicate that alternative road salts (to NaCl), and road salt additives can alter the abundance and composition of organisms in freshwater food webs at multiple trophic levels, even at low concentrations. Consequently, road salt alternatives and additives might alter ecosystem function and ecosystem services. Therefore, transportation agencies should use caution in applying road salt alternatives and additives. A comprehensive investigation of road salt alternatives and road salt additives should be conducted before wide‐scale use is implemented. Further research is also needed to determine the impacts of salt additives and alternatives on higher trophic levels, such as amphibians and fish. Abstract : Our results indicate that alternative road salts (to NaCl), and road salt additives can alter the abundance and composition of organisms in freshwater food webs at multiple trophic levels, even at low concentrations. Consequently, road salt alternatives and additives might alter ecosystem function and ecosystem services. Therefore, transportation agencies should use caution in applying road salt alternatives and additives. A comprehensive investigation of road salt alternatives and road salt additives should be conducted before wide‐scale use is implemented. Further research is also needed to determine the impacts of salt additives and alternatives on higher trophic levels, such as amphibians and fish.